Health professional education and practice in preventing and controlling infections in New Zealand: a review to inform strategies for enhancing practitioner competencies and patient safety. Issue 1 (30th December 2020) - Gulliver, Linda; Brooks, Heather; Kinniburgh, Linda; Aburn, Rebecca; Stodart, Jo; Rudland, Joy
Abstract : Objective: Quality assurance for reducing infections is a key objective of the WHO's global action plan targeting antimicrobial resistance, yet no studies have employed a multifaceted approach to review health professional education and practice in infection prevention and control (IPC). This study completed such a review. Methods and analysis: New Zealand medical and nursing curricula were analysed for IPC-related teaching and assessment. Clinicians (undergraduate to senior) received peer-expert evaluation while performing procedures demonstrating IPC competencies. Patient and clinician self-evaluation followed. Hospital IPC practice monitoring was also reviewed. Results: Medical curricula had approximately twice the total IPC-related theory compared with nursing (79.71 vs 41.66 hours), emphasising microbiology. IPC theory in nursing curricula was applied, emphasising health and safety. Junior nursing students were rigorously taught (16.17 hours) and assessed (2.91 hours) in practical IPC competencies, whereas little practical instruction (2.62 hours) and no formal assessment existed for junior medical students. IPC teaching chiefly occurred during medical students' senior clinical years, and was opportunistic, rotation-specific or in introductory sessions. Senior medical and nursing students were expected to be IPC-proficient but no formal assessment occurred. Peer review generally revealed satisfactory practice, however both professions had lapses with hand hygiene, asepsis and incorrect donning, removal and use of personal protective equipment. Clinician confidence in providing and being peer-reviewed for best IPC practice, and patients' confidence in receiving best IPC care, was positively associated with clinician experience. Trainee interns, whose confidence in IPC practice was not matched by the same desire for monitoring/feedback as senior colleagues, were the exception. Conclusion: Multifaceted approaches to IPC quality assurance have utility in identifying gaps, reducing infection transmission and reassuring staff and patients.